PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA SWALAYAN SURYA DI SUKABUMI BANDAR LAMPUNG - Ariza Karina Putri (Business and Enterpreneurship Journal (BEJ), 2023)
This study aims to determine the effect of service quality and customer satisfaction on customer loyalty at Surya Supermarkets in Sukabumi, Bandar Lampung. Furthermore, the data collection technique used in this study was a sampling technique taken by a set number of 50 respondents. Data collection was carried out using a questionnaire and hypothesis testing. In this study the researchers used the t test method and the Coefficient of Determination test with the help of the SmartPLS3 program. Based on the table of test results for the coefficient of determination test, the magnitude of R Square (R2) is 0.700. These results indicate that 70% indicates that the variable service quality and customer satisfaction, the customer loyalty variable is 70%. The results show that the variable Quality of Service with Customer Loyalty shows a path coefficient value of 0.247 with a t value of 2.804. This value is greater than t table (0.60). This result means that Service Quality has a positive and significant relationship to Customer Loyalty. And the results of the second test show that the relationship between customer satisfaction and customer loyalty variables shows a path coefficient value of 0.638 with a t value of 6.517. This value is greater than t table (0.60). This result means that Customer Satisfaction has a positive and significant influence on Customer Loyalty Performance.  Keywords : Service Quality, Customer Satisfaction, and Customer Loyality